Investigating invention : a challenge to the primacy of the written text - Pan, Esther (Department of Drama, 2016)
This paper investigates different ways of writing as creative invention for the writer/director/deviser. Three forms of writing are examined: the playwright as author of the dramatic text, the devising group as author of the dramatic and/or performance text, and the director as author of the mise en scene. In the first chapter the playwright as author is examined in relation to a historical view of the dramatic text. My own background as a playwright is treated in the context of the challenge to the written text experienced by contemporary playwrights as visual and physical elements of performance gain increasing importance. In the second chapter the devising group is addressed as author of the dramatic and/or performance text. Potential benefits of improvisation and devising are explored, as well as drawbacks of the devising process when compared to the process of writing a dramatic text as a playwright. In chapter three the director is scrutinised as the author of the mise en scene. The director's choice of a sign system and different methods of writing the performance text are weighed in view of their efficacy in creating a performance code that is readable by an audience. In the conclusion the three types of writing are evaluated, and the benefits and challenges of devising the dramatic and/or performance text are weighed; the devising process is regarded as an augmentation of a traditional writing process.